2002
DOI: 10.1055/s-2002-22699
|View full text |Cite
|
Sign up to set email alerts
|

New Organocatalysts for the Asymmetric Catalytic Epoxidation of Alkenes Mediated by Chiral Iminium Salts

Abstract: New iminium salt organocatalysts for catalytic asymmetric epoxidation based upon dibenzazepinium salts are reported, providing ee of up to ca 60%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 4 publications
0
24
0
1
Order By: Relevance
“…[13] This provides evidence that the active oxidant in this instance is indeed monoperoxysulfate. As described above, the percarbonate-driven system provides lower ees.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…[13] This provides evidence that the active oxidant in this instance is indeed monoperoxysulfate. As described above, the percarbonate-driven system provides lower ees.…”
Section: Introductionmentioning
confidence: 66%
“…This is puzzling when it is considered that under both our original Oxone-and TPPP-mediated conditions this conversion proceeds with ees of between 17 and 49% for these substrates. [13] As a further test, catalyst 2 was also evaluated. In this instance, low to moderate ees were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Page and co-authors reported the application of another chiral iminium salt-catalyzed epoxidation as key step in the first highly enantioselective synthesis of (+)-scuteflorin A, one of the numerous and pharmacological active compounds recently isolated from Scutellaria species (Scheme 47) [102]. A previously reported chiral iminium salt 115 [103] served as organocatalyst under non aqueous conditions, to epoxidize the starting Z-alkene 116 into the corresponding key enantiopure epoxide 117 in 97% yield. Epoxide hydrolysis/oxidation and esterification completed the synthesis.…”
Section: Asymmetric Organocatalyzed Epoxidations As Key Stepsmentioning
confidence: 99%
“…[5] We were the first to report iminium salt catalysts based on tetrahydroisoquinolines bearing an exocyclic chiral substituent on the nitrogen atom, [6] and a dioxane-based substituent has proved to be optimum for both yield and induction of enantioselectivity. [7][8][9] Three of the most successful catalysts are the dihydroisoquinolinium salt 3a, [9,10] biphenylazepinium salt 4, [8,9,11] and binaphthalene-azepinium salt 5, which can provide enantiomeric excesses of up to 97%. [9,12] The standard iminium salt epoxidation conditions employ the triple salt Oxone (2 KHSO 5 ·KHSO 4 ·K 2 SO 4 ) as a stoichiometric oxidant, sodium carbonate, and acetonitrile:water as the solvent mixture (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%